2022
DOI: 10.1002/cplu.202200187
|View full text |Cite
|
Sign up to set email alerts
|

BiVO4 Photoanodes for TEMPO‐Mediated Benzyl Alcohol Oxidation in Organic Media

Abstract: The photoelectrochemical production of fuels, exemplified by light‐driven water splitting to hydrogen and oxygen, offers a sustainable option to offset dependence on fossil fuels. A low‐cost, efficient, and stable photoelectrochemical approach to solar fuels remains elusive but using similar materials and photoelectrodes for chemical production or biomass conversion offers an appealing alternative. This work reports a facile method for fabricating pristine (undoped) BiVO4 photoanodes to carry out TEMPO‐mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…The fabrication of a dense WO 3 coating film limits exposure of the FTO surface to the electrolyte and provides a suitable substrate for the direct deposition of BiVO 4 layers. , Figure C,D shows top-down views of BiVO 4 two-layer films deposited on top of FTO|WO 3 (1L), where BiVO 4 appears as an aggregated network of particles with morphological features typical of monoclinic BiVO 4 . Previously prepared two-layer coatings of BiVO 4 without the WO 3 underlayer have displayed less aggregated, more open surface morphology . The cross-sectional images in Figure E,F indicate the deposition of uniform WO 3 and BiVO 4 films to give a defined sequential layering within the heterojunction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fabrication of a dense WO 3 coating film limits exposure of the FTO surface to the electrolyte and provides a suitable substrate for the direct deposition of BiVO 4 layers. , Figure C,D shows top-down views of BiVO 4 two-layer films deposited on top of FTO|WO 3 (1L), where BiVO 4 appears as an aggregated network of particles with morphological features typical of monoclinic BiVO 4 . Previously prepared two-layer coatings of BiVO 4 without the WO 3 underlayer have displayed less aggregated, more open surface morphology . The cross-sectional images in Figure E,F indicate the deposition of uniform WO 3 and BiVO 4 films to give a defined sequential layering within the heterojunction.…”
Section: Resultsmentioning
confidence: 99%
“…While purged with N 2 , the reactor was not completely sealed from atmosphere and a FE of 45% was found for the production of benzaldehyde. This result was unexpectedly low given our previous findings . Control experiments with an air-saturated solution revealed that the FE was contingent on excluding the presence of oxygen in the reactor.…”
Section: Resultsmentioning
confidence: 99%
“…117 Recent studies have examined the utility of coupling bismuth vanadate, a 2.4 eV band gap n-type semiconductor, with N -oxyl mediators to achieve specific organic oxidation reactions such as the conversion of 5-hydroxymethyfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA) with (2,2,6,6-tetramethylpiperidin-1-yl)oxyl (TEMPO) 118,119 or the formation of 1-tetralone from tetralin mediated by N -hydroxysuccinimide (NHS). 120 Specifically in the case of benzyl alcohol oxidation, BiVO 4 -based photoanodes, both with NHS 120 and TEMPO, 13 have demonstrated the production of benzaldehyde with faradaic efficiencies of ≥85%. This reaction has also been the focus of dye-sensitized photoanode based systems relying on TEMPO to mediate the production of benzaldehyde both with TEMPO being dissolved in the electrolyte 121 and with surface bound chromophore–TEMPO dyad or triad type surface adsorbates.…”
Section: Aminoxyl Mediated Photoelectrochemical Oxidation Approachesmentioning
confidence: 99%
“…With this motivation, Sherman, Yoo, and Leem research groups have developed photoelectrocatalytic processes for oxidative chemical transformations in primary aliphatic and/or benzyl alcohols by combining a DSPEC and aminoxyl radical mediators (ARMs). 13–19…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation